(untitled) (Research, Society and Development, 2021)
Dental trauma is a public health problem due to the damage it can cause in children and adolescents. The injuries caused can be classified according to the etiology and consequences caused to the individual. Physical educators are professionals who commonly face traumatic injuries, since practitioners are more exposed to this situation. Therefore, knowing the correct management for a traumatized tooth is extremely important for the prognosis of the case. The objective of this work is to evaluate the knowledge of physical education professionals from the Association of Physical Education Professionals (APEF) in the city of Patos de Minas regarding a possible case of dental avulsion and fracture. To carry out this research, 53 professionals answered a questionnaire with objective questions about the topic of dental avulsion, through the Google Forms platform. At the end of the study, professionals who showed interest received a free feedback on the topic addressed. It was possible to observe that most of the sample is composed of specialists, with 11 to 20 years of experience. As for the conduct with an avulsed dental element, only 7.5% of the participants answered correctly, which may be a reflection of the vast majority not having studied the subject during their academic training, demonstrating insufficient knowledge regarding this situation.